Efektivitas Teknologi Nano dalam Menghambat Bakteri Vibrio harveyi - Tusyahrah, Aulia; Alifia, Frida; Cahyono, Indra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Vibrio harveyi is a Gram-negative marine bacterium from the genus Vibrio known for its ability to emit light (bioluminescence). This bacterium is rod-shaped, moves using flagella at one end, has facultative anaerobic properties, and thrives in environments with high salt content (halophilic). Vibrio harveyi is often found in tropical and subtropical marine waters, especially in coastal ecosystems. Nanotechnology, which is the focus of this study, is a technology based on objects (structures) that are at the nanometer level, often used in biomedical and environmental applications. The purpose of this study was to determine the effect of SLS (nanoenzyme) in inhibiting the growth of Vibrio harveyi, which can cause disease in various marine organisms, including fish and shrimp. The method used in this study was experimental with a quantitative approach, where various concentrations of SLS were tested on bacterial growth. This study was conducted from June to July 2024, under controlled laboratory conditions. The results of this study indicate that the effect of SLS (nano enzyme) cannot inhibit the growth of Vibrio harveyi bacteria at various concentrations, namely 100%, 40%, 20%, and 10%. This is thought to be due to the particle size of the nano, where a smaller nanoparticle size can increase its effectiveness as an antimicrobial. In addition, several other methods need to be tested on SLS (nano enzyme) to understand further its ability to inhibit the growth of Vibrio harveyi bacteria, such as combining with other antimicrobial materials or modifying the nanoparticle structure.